Improvement of Quality in Technical Education through Application of Quality Circle Strategy - Gahlot, P. S. (Journal of Engineering Education Transformations, 1994)
With the modern world of competition, no country or organisation can afford to produce poor quality products. For producing good quality product, the human mind is to be utilised in addition to physical skills.